2019
DOI: 10.1017/s0950268819000402
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisations with infections related to antimicrobial-resistant bacteria from the French nationwide hospital discharge database, 2016

Abstract: Massive use of antibiotics has led to increased bacterial resistance to these drugs, making infections more difficult to treat. Few studies have assessed the overall antimicrobial resistance (AMR) burden, and there is a paucity of comprehensive data to inform health policies. This study aims to assess the overall annual incident number of hospitalised patients with AMR infection in France, using the National Hospital Discharge database. All incident hospitalisations with acute infections in 2016 were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…As reported in a previous study, 9 numerous hospitalizations with an infection PD are not associated with an identified infecting microorganism code. Two groups were then defined, one with at least one microorganism recorded and a second without.…”
Section: Study Populationsupporting
confidence: 69%
See 4 more Smart Citations
“…As reported in a previous study, 9 numerous hospitalizations with an infection PD are not associated with an identified infecting microorganism code. Two groups were then defined, one with at least one microorganism recorded and a second without.…”
Section: Study Populationsupporting
confidence: 69%
“…(2019; Supplementary Material: Table 1 ). 9 In case of multiple infections or multiple organisms or resistance status, the infection cannot be properly identified since the database does not allow linking an infection with the responsible bacteria or bacteria with their resistance status, except for some specific combined codes (such as methicillin-resistant S.aureus , MRSA). To reduce the number of stays excluded because of unrecorded microorganism/resistance pair, a previously elaborated algorithm 9 was used to retain some of such hospitalizations in the selected population.…”
Section: Study Populationmentioning
confidence: 99%
See 3 more Smart Citations